Sonographic assessment of uterine scar thickness and associated factors among pregnant women with previous caesarean sections at a tertiary hospital in Tanzania - Jerome, Karoli; Nyakunga, Feredina J.; Matovelo, Dismas; Kajura, Alphaxard; Ngoya, Patrick S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Uterine scar thickness has a practical application on the safe mode of delivery for pregnant woman with previous cesarean section (CS) lower uterine segment (LUS) scar. The study aimed to assess sonographic uterine scar thickness and associated factors among pregnant women with previous CS at a tertiary hospital in Mwanza, Tanzania. Methods: An analytical cross-sectional analytical study was carried out at a tertiary hospital in Mwanza, Tanzania that included pregnant women with previous CS at term (≥ 36 weeks of gestation). Transabdominal obstetric ultrasound was performed. A uterine scar thickness was categorized as thin or thick using a cut off of 2.5 mm. Data were presented using descriptive statistics and analysed. A p value of less than 0.05 considered statistically significant. Results: About 113 out of 400 women (28.3%) had thin uterine scars. Inter-pregnancy interval (p<0.001), history of wound infection (p=0.01) and placenta location (p=0.001) were significant factors associated with uterine scar thickness. On adjusted logistic regression analysis, inter-pregnancy interval [aOR (95% CI) =2.35 (1.38-3.99), p=0.002], estimated fetal weight [aOR (95% CI) =0.54 (0.34-0.87), p=0.01] and anterior placenta location [aOR (95% CI) =0.55 (0.34-0.90), p=0.02] were factors most likely to predict uterine scar thickness. Conclusions: Uterine scar thickness assessment by sonography in pregnant women with previous cesarean sections can be easily integrated in an obstetric ultrasound. We recommend its routine application, and in combination with risk factors may guide decision on the mode of delivery and help prevent adverse maternal and fetal outcomes.